2013
DOI: 10.1139/cjb-2012-0258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the moss Homalothecium lutescens in relation to habitat age and structure

Abstract: Relationships between genetic (allozyme) variation and landscape age and structure were investigated in 17 calcareous grassland demes of the moss Homalothecium lutescens (Hedw.) H. Rob. on the Baltic island of Öland. Mean within-deme gene diversity (H S = 0.152) was moderate compared with other bryophyte studies, and the between-deme proportion of the total diversity (G ST = 0.100, Jost's D = 0.011) was low but significantly different from zero. Clonal mixing, measured as the proportion of two adjacent shoots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
1
15
1
Order By: Relevance
“…Surprisingly, there was no eff ect at the smallest scale (1 km), even when the actual number of occurrences of the species in the surrounding area was used as the explanatory variable. However, as noted in the introduction several other studies on genetic structure and occurrence patterns suggest more restricted dispersal at a landscape scale (Sn ä ll et al 2004a, Hutsem é kers et al 2013, Korpelainen et al 2013, Rosengren et al 2013. Initially, this appears to be counterintuitive since we know that there is a steep decline in deposition of diaspores (also shown for spores) from a point source (S ö derstr ö m and Jonsson 1989, Bullock and Clarke 2000, Roads and Longton 2003, Sundberg 2005, L ö nnell et al 2012.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Surprisingly, there was no eff ect at the smallest scale (1 km), even when the actual number of occurrences of the species in the surrounding area was used as the explanatory variable. However, as noted in the introduction several other studies on genetic structure and occurrence patterns suggest more restricted dispersal at a landscape scale (Sn ä ll et al 2004a, Hutsem é kers et al 2013, Korpelainen et al 2013, Rosengren et al 2013. Initially, this appears to be counterintuitive since we know that there is a steep decline in deposition of diaspores (also shown for spores) from a point source (S ö derstr ö m and Jonsson 1989, Bullock and Clarke 2000, Roads and Longton 2003, Sundberg 2005, L ö nnell et al 2012.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in a recent study of deposition patterns of Sphagnum spores, it was found that a connectivity of 200 km provided the best explanation for the deposition (Sundberg 2013). However, as noted in the introduction several other studies on genetic structure and occurrence patterns suggest more restricted dispersal at a landscape scale (Sn ä ll et al 2004a, Hutsem é kers et al 2013, Korpelainen et al 2013, Rosengren et al 2013. In light of the investigations suggesting good dispersal capacities, our result should not be altogether surprising, and it is even possible that we could have found a stronger relationship between colonization rates and extent of clay-dominated soils if we had implemented a design that allowed us to investigate even larger scales.…”
Section: Discussionmentioning
confidence: 95%
“…Central European calcareous grasslands represent local biodiversity hotspots due to their long existence, habitat diversity, and species richness (Steffan-Dewenter and Tscharntke 2002; Karlik and Poschlod 2009;Poschlod 2017). More precisely, they constitute valuable habitats for many specialised, rare, and endangered plant or insect species and are, therefore, considered as key areas for biodiversity conservation in agricultural landscapes (Raatikainen et al 2009;Rosengren et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most probably haplotypes additional to these occurred in the lowlands during the early post‐glacial period. Genetic diversity in a population usually increases with time when a species is abundant and the connectivity among populations is good (Cronberg, ; Wang et al ., ; Rosengren et al ., ), but habitat fragmentation leading to small and isolated populations negatively affects their genetic diversity (Aguilar et al ., ). Thus, when the vegetation of the Swedish lowlands gradually closed, the three largest extant lowland populations of R. rugosum became smaller and increasingly isolated from each other and from those of the mountain range.…”
Section: Discussionmentioning
confidence: 99%